Thieme Chemistry Journals Awardees – Where Are They Now?Improved Fmoc Deprotection Methods for the Synthesis of Thioamide-Containing Peptides and Proteins - Szantai-Kis, D. Miklos; Walters, Christopher R.; Barrett, Taylor M.; Hoang, Eileen M.; Petersson, E. James (Synlett, 2017)
Site-selective incorporation of thioamides into peptides and proteins provides a useful tool for a wide range of applications. Current incorporation methods suffer from low yields as well as epimerization. Here, we describe how the use of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) rather than piperidine in fluorenylmethyloxycarbonyl (Fmoc) deprotection reduces epimerization and increases yields of thioamide-containing peptides. Furthermore, we demonstrate that the use of DBU avoids byproduct formation when synthesizing peptides containing side-chain thioamides.
Keywords: peptides; sulfur; solid-phase synthesis; protecting groups; proteins